Osteopathic Representation in Orthopaedic Literature: A 25-Year Analysis of Publication Trends of Former AOA Residency Programs and Osteopathic Medical Schools - Ibraheem Qureshi, BS; Troy B. Puga, DO; Hans Drawbert, MD; Michael E. Muncy, DO; John T. Riehl, MD (JBJS Open Access)
Background:. Orthopaedic surgery remains one of the most competitive specialties. Osteopathic candidates have recently matched at lower rates than allopathic students. One disparity that may exist is research, which has become a critical component of candidate applications. The aim of this study was to examine the representation of osteopathic-affiliated first authors, senior authors, and overall osteopathic-affiliated authors, in the top 25 leading US orthopaedic journals published between 2000 and 2024. Methods:. A retrospective bibliometric review was conducted on articles published from 2000 to 2024 in orthopaedic journals. Journals were selected based on their h-index score. Institutional affiliations were used to identify osteopathic authors. Articles with a majority of authors from foreign institutions were excluded. T-tests and chi-squared tests were used to assess continuous and categorical variables. Multivariate regression identified factors influencing osteopathic authorship. Results:. Nine hundred fifty-eight articles included osteopathic authors. 570 of 958 articles with osteopathic authors were published after the American Osteopathic Association-American Council for Graduate Medical Education (AOA-ACGME) merger. Senior osteopathic authorship significantly increased the osteopathic author makeup of articles, with the average number of osteopathic authors per article increasing from 0.02 to 2.93 (p < 0.001). After the merger, articles with at least 1 osteopathic author increased from 1.5% of all articles to 3.3% of all articles (p < 0.001). When looking at only osteopathic articles before and after the merger, there was a significant increase from 1.82 to 2.22 osteopathic authors per article (p < 0.001). Senior osteopathic authorship was also found to significantly increase the odds of having a first osteopathic author (OR: 213.34; 95% CI [165.65, 275.64]; p < 0.001). The merger has significantly increased the odds of having at least 1 osteopathic author in an article (OR: 2.02; 95% CI [1.76, 2.31]; p < 0.001). Conclusions:. Osteopathic physicians, students, and institutions remain underrepresented in orthopaedic literature. However, the presence of senior osteopathic authors and the AOA-ACGME merger have positively influenced osteopathic authorship. These findings suggest that reducing the divide between osteopathic and allopathic education, along with enhancing osteopathic mentorship, may help address academic disparities in orthopaedics. Level of Evidence:. Level III; Retrospective comparative study. See Instructions for Authors for a complete description of levels of evidence.